Confidence : transform the way you feel so you can achieve the things you want - Yeung, Rob (2013)
'Confidence' combines the best methods from cognitive behavioural therapy, sports psychology, neuro-linguistic programming, positive psychology and much more. Dr Rob Yeung, psychologist and coach, shows how to challenge your fears, build your confidence and achieve your goals in life.
Previous edition: 2011.
Includes bibliographical references and index.
Keywords: Self-confidence.